The blood‐borne sialyltransferase ST6Gal‐1 is a negative systemic regulator of granulopoiesis. Issue 2 (26th May 2017) - Dougher, Christopher W. L.; Buffone, Alexander; Nemeth, Michael J.; Nasirikenari, Mehrab; Irons, Eric E.; Bogner, Paul N.; Lau, Joseph T. Y.
Abstract : Elevating circulating ST6Gal‐1 sialyltrasferase blunts granulopoiesis at the level of GMP. Abstract : Responding to systemic demands in producing and replenishing end‐effector blood cells is predicated on the appropriate delivery and interpretation of extrinsic signals to the HSPCs. The data presented herein implicate the systemic, extracellular form of the glycosyltransferase ST6Gal‐1 in the regulation of late‐stage neutrophil development. ST6Gal‐1 is typically a membrane‐bound enzyme sequestered within the intracellular secretory apparatus, but an extracellular form is released into the blood from the liver. Both human and murine HSPCs, upon exposure to extracellular ST6Gal‐1 ex vivo, exhibited decreased proliferation, diminished expression of the neutrophilic primary granule protein MPO, and decreased appearance of CD11b + cells. HSPC suppression was preceded by decreased STAT‐3 phosphorylation and diminished C/EBPα expression, without increased apoptosis, indicating attenuated G‐CSF receptor signaling. A murine model to raise systemic ST6Gal‐1 level was developed to examine the role of the circulatory enzyme in vivo. Our results show that systemic ST6Gal‐1 modified the cell surface of the GMP subset of HSPCs and decreased marrow neutrophil reserves. Acute airway neutrophilic inflammation by LPS challenge was used to drive demand for new neutrophil production. Reduced neutrophil infiltration into the airway was observed in mice with elevated circulatory ST6Gal‐1 levels. The blunted transition of GMPs into GPs in vitro is consistent with ST6Gal‐1‐attenuated granulopoiesis. The data confirm that circulatory ST6Gal‐1 is a negative systemic regulator of granulopoiesis and moreover suggest a clinical potential to limit the number of inflammatory cells by manipulating blood ST6Gal‐1 levels.